Cut it out : the C-section epidemic in America - Morris, Theresa (New York University Press, 2013)
"Thoughtful and engaging study." - Beth Mintz, author of The Power Structure of American Business "A must-read not only for women's health advocates and scholars of reproduction, but also for those engaged in health care policy." - Susan Markens, author of Surrogate Motherhood and The Politics of Reproduction "Morris takes you inside... with a critical eye as well as a compassionate ear." - Jennifer Block, author of Pushed